CYCLOTRON SPECTRAL INTENSITIES FROM AM-HER SYSTEMS - Qudah, Ali M (European Scientific Journal, ESJ, 2013)
The ordinary and extraordinary uncoupled Cyclotron radiation mode intensities, +I and −I respectively, are being calculated for radiative accretion shocks onto magnetic binary AM-Her systems. The calculation is being performed for accretion onto a primary white dwarf star having a 0.3 solar mass; radius cm R9*=x101.23. The calculation corresponds to the accretion rate Edd L=3.2x10-3accL . Here EddL is the Eddington accretion luminosity. At a given instant of time, variation of both modes intensities with harmonic numbers is investigated for various angles of observation. This is done for on axis accretion; where the geometric factor a0=500. The field on the pole is taken to be MG 12 B*=. Also for a certain direction and harmonic number, the time dependent intensities are being calculated for various fields; , B*=MG 23 17, 15 .